2020
DOI: 10.1101/2020.09.24.311597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human inbreeding has decreased in time through the Holocene

Abstract: SummaryThe history of human inbreeding is controversial. The development of sedentary agricultural societies may have had opposite influences on inbreeding levels. On the one hand, agriculture and food surplus may have diminished inbreeding by increasing population sizes and lowering endogamy, i.e. inbreeding due to population isolation. On the other hand, increased sedentism, as well as the advent of private property may have promoted inbreeding through the emergence of consanguineous marriage customs or via … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…Compared to the other samples, the HG genomes, and in particular Bichon and SF12, show a larger proportion of short (2-10Mb) Runs of Homozygosity (ROHs, Fig. 2c ), in keeping with previous results 17,28,29 . This is indicative of higher levels of remote inbreeding within European HGs, likely due to smaller population sizes as corroborated by MSMC2 analyses ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Compared to the other samples, the HG genomes, and in particular Bichon and SF12, show a larger proportion of short (2-10Mb) Runs of Homozygosity (ROHs, Fig. 2c ), in keeping with previous results 17,28,29 . This is indicative of higher levels of remote inbreeding within European HGs, likely due to smaller population sizes as corroborated by MSMC2 analyses ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…2C). Contrary to previous interpretations (25,31), HGs are generally found to have larger population sizes than contemporary early farmer populations (Fig. 3A) which explains why they show close genetic affinities on the MDS (Fig.…”
Section: Evolutionary Insights Gained From Explicit Demographic Modelingcontrasting
confidence: 80%
See 1 more Smart Citation
“…As reported earlier ( 8, 12, 21, 23 ), Aşıklı, Boncuklu, and Caucasus pre-Neolithic genomes carried large numbers of ROH, indicative of small population size. Certain Neolithic genomes (e.g., WC1, Ash128) also showed a “right-shift” when plotting the number versus sum of ROHs, indicative of recent inbreeding ( 34 ) (Fig. 5B-C).…”
Section: Resultsmentioning
confidence: 99%
“…We performed linear regression using short ROH (4-8 cM) in present-day genomes to create a baseline that represents solely drift with no recent inbreeding. Right-shift from the baseline indicates that parents of this individual could be close-kin, whereas individuals that are around the baseline, and also have a relatively high number of ROH come from a population with potentially low N e (effective population size) ( 34 ). We filtered out ROHs <4 cM following the original hapROH publication which suggested that the method can detect ROH >4 cM ( 33 ).…”
Section: Methodsmentioning
confidence: 99%